Evaluation of soil temperatures at agroclimatological station Pohořelice - Hana Pokladníková; Jaroslav Rožnovský; Tomáš Středa (Soil and Water Research, 2008)
Soil temperatures were analysed for the climatological station Pohořelice during the period of 1961-2000. According to the agroclimatic zoning, this region is a part of warm macroarea, mainly warm area, mainly dry subarea, and a district of mainly cold winter. The average annual air temperature is 9°C and the average year precipitation total is 475 mm. For the characterisation of the soil temperature were used the average monthly soil temperature determined from daily averages, maximal monthly soil temperature determined on the basis of daily maximums, and minimal monthly value determined on the basis of daily minimums. In the Czech Hydrometeorological Institute, the soil temperature was measured in the observation terms at 7:00, 14:00 and 21:00 local mean time. These temperature characteristics were assessed for the depths of 5, 10, 20, 50, and 100 cm. The longterm average annual temperature for the depths measured varies from 10.0°C (at 20 cm) to 10.4°C (at 100 cm). From the longterm viewpoint, the warmest month for the depths of 5, 10, and 20 cm is July, the coldest one is January, and for the depths of 50 and 100 cm the warmest month is August and the coldest one is February. For the classification of single months, the average monthly soil temperature for the respective month was compared with the longterm average soil temperature of 1961-2000. According to the average monthly soil temperature and its standard deviation, the months of the evaluated period were divided into seven categories: thermally normal months, warm months, very warm months, extraordinary warm months, cold months, very cold months, and extraordinary cold months.